Avaliação do perfil oxidativo e inflamatório na infecção por Influenza B - Bulegon, Jovana Simonetti (2023)
The influenza B virus, the causative agent of influenza, is still one of the main causes of respiratory diseases that affects the world's population and causes thousands of deaths worldwide. Oxidative stress, may be associated with this disease, caused by alterations in the production of reactive oxygen species (ROS) and the imbalance of antioxidants, which leads to the oxidation of biomolecules and loss of their biological functions. The sulfhydryl enzyme delta-aminolevulinate dehydratase (δ-ALA-D) may be inhibited in pro-oxidant situations and this inhibition also causes an increase in the production of free radicals. Thus, the δ-ALA-D enzyme may be an indirect marker of oxidative stress. Furthermore, there is the production of pro-inflammatory cytokines, which, in excess, can also result in injuries to the infected organism and result in cell and tissue damage and consequent serious conditions. In this context, considering the thousands of infections and deaths from influenza B every year, the objective is to verify the oxidative and inflammatory profile and the activity of the δ-ALA-D enzyme in the infection by the influenza B virus. Blood samples from 50 participants were evaluated as influenza B virus and 30 healthy participants. The oxidative stress quantified in the analyzed groups were through thiobarbituric acid reactive substances (TBARS), protein (PSH) and nonprotein (NPSH) thiol groups, vitamin C levels (VIT C), plasma iron reduction ability (FRAP) and the enzyme delta-aminolevulinate dehydratase (δ-ALA-D). The inflammatory profile was analyzed by determining the levels of interleukin-2 (IL-2), interleukin-4 (IL-4), interleukin-6 (IL-6), interleukin-10 (IL-10), interleukin-17A (IL-17A), interferon-gamma (IFN-γ) and tumor necrosis factor alpha (TNF-α). The results showed that lipid peroxidation and levels of IL-6, IL-10, IL-17A and IFN-y were statistically higher in the group with influenza B. The activity of analyzed antioxidants, levels of thiols, vitamin C and FRAP, was significantly lower in those infected with the influenza B virus compared to the controls, as well as the activity of the δALA-D enzyme, in addition the enzyme showed a higher reactivation rate for those infected with influenza B. generation of oxidants, the depletion of the antioxidant system, reduced activity of the δ-ALA-D enzyme and an expression pattern of IL-6, IL-10, IL-17A and IFN-y during influenza B virus infection.